Survey on Linux Security and Vulnerabilities (International Journal of Engineering and Computer Science, 2014)
This paper is intended as overview of Linux security and different threads to server, network and workstation. SELinux, which is an implementation of Linux Security Modules (LSM), implements several measures to prevent unauthorized system usage. Security is a very broad concept, and so is the security of a system. All too often, people believe that a system is way more secure that it in practice is, but the biggest problems is still the human factor of the users; the possibility of careless or malicious users are commonly overlooked. Finally this paper concludes with providing list of some various common vulnerability, attacks and countermeasures.